Changes of DNA quality and meat physicochemical properties in bovine supraspinatus muscle during microwave heating. (6th November 2013) - Musto, Mauro; Faraone, Daniela; Cellini, Francesco; Musto, Elisa
Abstract BACKGROUND The responses of foods to microwave exposure are usually evaluated only in terms of physicochemical properties, thus undervaluing the importance of DNA in an authentication process by methods based on polymerase chain reaction (PCR). In this study, the time effect of microwave heating on some meat physicochemical properties and DNA quality has been investigated. RESULTS Cooking loss, instrumental colour, pH and other physicochemical parameters varied significantly during microwave cooking, reaching the lowest/highest values after 2.5 min of cooking. The exposure of meat to microwaves was found to affect characteristically the quality of extracted DNA (i.e. yield, purity and degradation). PCR products of both mitochondrial and nuclear regions were successfully observed in all samples. However, the band for large fragments became progressively fainter as treatment time increased. CONCLUSIONS Microwave heating caused physicochemical changes in bovine supraspinatus muscle and influenced characteristically the yield and integrity of the extracted DNA, indicating that an accurate DNA quantification and a rational choice of the genes (i.e. mtDNA versus nDNA, fragment size, etc.) to be amplified are fundamental in an authentication process by PCR‐based methods. © 2013 Society of Chemical Industry